Assessing Life Skills and Adolescent Mental Health: Cross-Cultural Adaptation and Psychometric Evaluation of the Life Skills Scale in Portugal - Ana Cristina Maia Rocha; Ana João; César Fonseca; Leonel Lusquinhos; Lara Guedes de Pinho (European Journal of Investigation in Health, Psychology and Education, 2026)
Life skills are cognitive, emotional and social competencies that help adolescents manage everyday demands and participate in school and social contexts. This study aimed to translate, culturally adapt and examine the psychometric properties of the European Portuguese Life Skills Scale (LSS). A cross-sectional methodological study included a convenience sample of 1807 Portuguese adolescents aged 13–19 years from public secondary schools in Central Portugal. The sample was randomly split for exploratory factor analysis (EFA; n = 903) and confirmatory factor analysis (CFA; n = 904). EFA supported an interpretable eight-factor solution explaining 50.7% of the variance. CFA compared the original ten-factor model with the EFA-derived eight-factor model. The ten-factor model showed significant standardised loadings (λ = 0.444–0.849) and comparatively better fit, with acceptable root mean square error of approximation (RMSEA = 0.045) and standardised root mean square residual (SRMR = 0.062), although the comparative fit index (CFI = 0.855) and Tucker–Lewis index (TLI = 0.849) remained below preferred thresholds. Internal consistency was satisfactory to excellent (α = 0.782–0.963; ω = 0.783–0.964). Average variance extracted (AVE) and heterotrait–monotrait ratio (HTMT) analyses provided partial evidence of convergent validity and additional support for discriminant validity. Supplementary multi-group CFA provided preliminary support for measurement invariance across female and male adolescents. Findings provide initial support for the European Portuguese LSS as a multidimensional measure of adolescent life skills.